Avatars in mixed reality meetings: A field study of avatar facial realism on felt and perceived emotion - Dobre, Georgiana Cristina; Wilczkowiak, Marta; Gillies, Marco; Pan, Sylvia Xueni; Rintel, Sean (EMRN 2024: A Metaverse For Good, 2024)
We conducted a within-subjects study to examine how realistic faces and cartoon faces on avatars effect communication, task satisfaction, sense of presence, and emotional state perception in mixed reality meetings. Over the course of two weeks, six groups of co-workers (14people) held recurring meetings using Microsoft HoloLens2 devices, each person embodying a personal full-body avatar with either a realistic face or cartoon face. Half of the groups started with the realistic face avatar and switched to the cartoon face version halfway through (RC condition), and the other half with the cartoon-face avatar first (CR condition). For this paper, we focus on our results of emotion felt and perceived. We found that participants reported more positive emotions with the realistic face avatar but only in the RC condition. This positive emotion also seemed to have reduced over time. The realistic face avatar also caused more error in judgement of their colleagues emotions, and again this was worse in the RC condition.